MiR-146a-5p Mimic Inhibits NLRP3 Inflammasome Downstream Inflammatory Factors and CLIC4 in Neonatal Necrotizing Enterocolitis - Chen, Jianglong; Chen, Tong; Zhou, Jin; Zhao, Xiuhao; Sheng, Qingfeng; Lv, Zhibao (Frontiers in Cell and Developmental Biology, 2021)
Objects: Necrotizing enterocolitis (NEC) is a gastrointestinal emergency with severe inflammation storm, intestinal necrosis and perforation. MicroRNA-146a-5p (miR-146a-5p), has been reported as a valuable anti-inflammation factor in various intestinal inflammatory disorders. However, the role of miR-146a-5p in NEC and its effect on the nucleotide-binding domain as well as leucine-rich repeat-containing protein 3 (NLRP3) inflammasomes are still unknown. This study aimed to investigate the role of miR-146a-5p and NLRP3 inflammasomes in the NEC development. Methods: The expression level of miR-146a and NLRP3 inflammasomes were investigated. Then the mechanism of miR-146a-5p regulating the activation of NLRP3 inflammasomes was explored. Finally, to identify the effects of miR-146a-5p on NEC in vivo, NEC mice was transinfected with miR-146a-5p overexpression adenovirus before the occurrence of NEC. Results: NLRP3 inflammasomes were activated in NEC intestinal samples in both human and mice, and miR-146a-5p expression level was increased and mainly expressed in the macrophage of the affected intestine. In vitro, only miR-146a-5p mimics inhibited the NLRP3 inflammasomes activation by reducing the chloride intracellular channel protein 4 (CLIC4) cellular membrane translocation in THP-1 cell line, and this only occurred under mild/moderate LPS concentration. MiR-146a-5p overexpression adenovirus transfection reduced the CLIC4 cellular membrane translocation, and inhibited NLRP3 activation in vivo. After the transfection of miR-146a-5p adenovirus, the survival rate of NEC mice was increased, and intestinal injury was ameliorated. Conclusion: MiR-146a-5p inhibited the NLRP3 inflammasomes activation by reducing the CLIC4 cellular membrane translocation in NEC. Besides, miR-146a-5p could attenuate the inflammation and intestinal injury in NEC-affected intestine.